Migrasome, a migration-dependent organelle - Zhang, Fuyong; Liu, Wendong; Mao, Yunpeng; Yang, Yuhao; Ling, Chenxi; Liu, Ya; Yao, Feng; Zhen, Yunfang; Wang, Xiaodong; Zou, Mincheng (Frontiers in Cell and Developmental Biology, 2024)
Migrasomes are organelles produced by migrating cells that form on retraction fibers and are released during cell migration. Migrasomes are involved in physiological and pathological processes such as intercellular communication, cell homeostasis maintenance, signal transduction, disease occurrence and development, and cancer metastasis. In addition, methods and techniques for studying migrasomes are constantly evolving. Here, we review the discovery, formation process, regulation, and known functions of migrasomes, summarize the commonly used specific markers of migrasomes, and the methods for observing migrasomes. Meanwhile, this review also discusses the potential applications of migrasomes in physiological processes, disease diagnosis, treatment, and prognosis, and looks forward to their wider application in biomedicine. In addition, the study of migrasomes will also reveal a new perspective on the mechanism of intercellular communication and promote the further development of life science.